Association between Innovative Entrepreneurial Orientation, Absorptive Capacity, and Farm Business Performance. Issue 1 (25th June 2014) - Gellynck, Xavier; Cárdenas, Jorge; Pieniak, Zuzanna; Verbeke, Wim
ABSTRACT A growing interest emerges with regard to how entrepreneurship and innovation can contribute to the success and well‐being of the farmers. The main objective of the study is to develop and test a model, which emphasizes the relationship of trust and innovative entrepreneurial orientation on absorptive capacity in an agricultural context. This article examines also the effect of absorptive capacity on innovation as well as the connection of both innovative entrepreneurial orientation and innovation outcome on farm business performance. Cross‐sectional data were collected from a sample of 199 banana farmers in 2008‐2009 in Ecuador. A structural equation modeling approach has been applied to validate the hypothesized model. The findings show that all relationships established in the model are significantly and positively associated, except for the linkage between innovation outcome and farm business performance. [EconLit citation: L260; O310; Q160]